Intellectuals and Service to the People: The Role of Academics in Increasing the Capacity of Sustainable Societies - Abdul Azis; Nurasiah; Ferdi Riansyah; Dedi Sufriadi (Universitas Syiah Kuala and Collaboration Yayasan Yusda Edu Indonesia, 2025)
This study aims to deeply understand the role of academics in building the capacity of sustainable societies through service practices based on social reflection and local values. The research approach uses a qualitative method with a phenomenological design, which focuses on the meaning of the subjective experiences of the academics and the communities involved. Data were obtained through in-depth interviews, participatory observations, and documentation of service activities in several communities in South Sulawesi over a six-month period. The results of the thematic analysis show three main themes, namely the transformation of the role of academics from instructors to social partners, the integration of local wisdom as a basis for sustainability, and critical reflection on the impact and value of service. These findings confirm that the success of community service is not only determined by the existence of the program, but by the quality of social relations and the co-learning process between academics and the community. This research provides a theoretical contribution to the development of the concept of academic citizenship as well as a practical contribution to strengthening university policies in encouraging participatory, reflective, and sustainable community service.